Correlates of Posttraumatic Stress Symptoms among Formerly Incarcerated, Homeless Women. (2nd August 2020) - Salem, Benissa E.; Hudson, Angela L.; Yadav, Kartik; Lucas, Jaemilyn; Toyama, Joy; Chen, Stephanie; Faucette, Mark; Ekstrand, Maria L.; Nyamathi, Adeline M.
Abstract: Posttraumatic stress symptoms are a pressing issue among women experiencing incarceration and homelessness. Baseline data were collected among formerly incarcerated homeless women (N = 130) who were on average 38.9 (SD = 11.36, range 19–64) years of age and recruited into a pilot randomized control trial (RCT) intervention program. A logistic regression was used to assess correlates of PTSD symptoms. The majority of the sample self-reported witnessing violence (85%) and had moderate PTSD symptoms (M = 1.61, SD = 1.62, range: 0–4). No past month drug use ( p  = 0.006), higher anger scores ( p  = 0.002), greater emotional support ( p  = 0.009), and psychological frailty ( p  = 0.02) were significantly associated with higher odds of PTSD symptoms. Moreover, women who experienced minor family conflicts had lower odds of PTSD symptoms relative to those that had family conflicts most of the time ( p  = 0.02). Similarly, controlling for all other variables, women who had a higher positive social interaction score also had lower odds of PTSD symptoms ( p  = 0.006). These findings are a call to action for academicians, service providers, and health practitioners to develop an intervention which integrates comprehensive PTSD screening, and discussion of ways to build coping skills, relationships with family and social networks, and utilizes a trauma-informed approach during reentry.